2017
DOI: 10.1002/pc.24696
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical performance of thermoplastic composites using bituminous coal as filler: Study of a potentially sustainable end‐use application for Appalachian coal

Abstract: This study evaluated the utilization of bituminous coal from the Appalachian basin as filler material in high density polyethylene (HDPE) composites. Three coal types including Pittsburgh No. 8, Kittanning, and Upper Freeport were evaluated. The impact of coal (0–60 wt%) and coupling agent (0–3 wt%) content on flexure and tensile properties of the coal/HDPE composites was investigated. In addition, coal surface chemistry was analyzed using Boehm analyses and compared to pine wood flour. Composite flexure stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
4
11
1
Order By: Relevance
“…Other studies by Chaharmhali et al 37 and Ratanawilai and Kampanart 38 found decreasing WPC flexural strength with increasing filler content. A similar decrease in the flexural strength of a polypropylenebased WPC was also reported by Sengupta et al 39 The increase in CPC flexural strength and modulus with the addition of 60 wt % coal was higher than the values reported by Phillips et al Overall, the greater flexural strength of the CPCs in this study, in comparison with prior work, 17 is a result of the stronger HDPE material used in this study in conjunction with optimal composite process parameters, namely, lower compounding temperatures, higher extrusion pressures, and injection molding of coupon samples, resulting in improved dispersion of the filler.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Other studies by Chaharmhali et al 37 and Ratanawilai and Kampanart 38 found decreasing WPC flexural strength with increasing filler content. A similar decrease in the flexural strength of a polypropylenebased WPC was also reported by Sengupta et al 39 The increase in CPC flexural strength and modulus with the addition of 60 wt % coal was higher than the values reported by Phillips et al Overall, the greater flexural strength of the CPCs in this study, in comparison with prior work, 17 is a result of the stronger HDPE material used in this study in conjunction with optimal composite process parameters, namely, lower compounding temperatures, higher extrusion pressures, and injection molding of coupon samples, resulting in improved dispersion of the filler.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
“…38,40 At high filler content, reinforced polymer composites have been shown to demonstrate lower flexural strength owing to agglomerated filler particles, due to poor dispersion acting as stress concentration sites causing failure. 17,36,40,41 On the other hand, the improved dispersion of coal in the polymer matrix, due to the fabrication processes, described in this paper, allowed better stress transfer to the filler resulting in improved flexural performance of the 60 wt % coal samples compared to that of the 40 wt % coal samples. The increase in the flexural modulus for CPCs may be attributed to the higher stiffness of the coal filler (flexural modulus of 2.2 ± 0.8 GPa measured for bituminous coal) 42 and the restricted movement of the polymer chains due to the filler.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Recently, several types of coal have been investigated to replace wood flour used in polymer composites. 14,15 A former study has shown that coal plastic composite (CPC) outperformed several commercially available WPC products in strength, oxidation, burn rate, ignition, and water absorption. 14 In addition, a preliminary life cycle analysis also indicated CPC manufacturing requires less energy and generates less greenhouse gas emissions than WPC manufacturing.…”
Section: Introductionmentioning
confidence: 99%